Corporate women in contemporary China : "We've always worked" - Peng, Xinyan (New York, NY : Routledge, 2022)
"Based on extensive, multi-sited ethnographic research, this book focuses on the culture of work in today's urban China, and how it has permeated beyond the workplace to shape bodily training, family life, and kinship and social relationships among young white-collar women in their twenties and thirties. Facing challenges to cope with the increasingly intensified dual burden of work and family, white-collar women are not turning their back to their jobs but are turning their bodies and homes into work. In an era when the state and society heighten pressure on individual young women's productivity and reproductivity at the same time, the book examines how white-collar women seek to protect their right to work, embody a work ethic, and make their reproductive life a productive domain. Integrating studies of labor, the body, gender, and kinship, this book shows how the work ethic of hard work and overtime work gets transposed from the office cubicle to gym and home, with labor discipline applying both at and away from work strictly defined. It thereby demonstrates how the emergence, embodiment, and extension of a work culture perpetuate the hegemony of the work ethic, and have exerted a profound impact on women's bodies, selves, and lives"--
Keywords: Businesswomen -- China; Women executives -- China; Women -- China -- Social conditions -- 21st century; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research